18Fluorine‐fluorodeoxyglucose positron emission tomography for assessment of deep digital flexor tendinopathy: An exploratory study in eight horses with comparison to CT and MRI. Issue 5 (20th June 2021) - Wilson, Sabrina; Spriet, Mathieu; Mur, Pablo Espinosa; Anishchenko, Sergey; Beylin, David; Katzman, Scott; Galuppo, Larry
Abstract: Lesions of the deep digital flexor tendon (DDFT) are a cause for foot lameness in horses. Positron emission tomography (PET) could provide valuable information regarding the metabolic activity of these lesions. The aims of this exploratory, prospective, methods comparison study were to assess the ability of 18 fluorine‐fluorodeoxyglucose ( 18 F‐FDG) PET to detect DDFT lesions and to compare the PET findings with CT and MRI findings. Eight horses with lameness due to pain localized to the front feet were included. Both front limbs of all horses were imaged with 18 F‐FDG PET, noncontrast CT, and arterial contrast‐enhanced CT; 11 limbs were also assessed using MRI. Two observers graded independently 18 F‐FDG PET, noncontrast CT, arterial contrast CT, T1‐weighted (T1‐w) MRI, and T2‐weighted (T2‐w)/STIR MRI. Maximal standardized uptake values were measured. Lesions were found in seven of 16 DDFT on PET, 12 of 16 DDFT on noncontrast CT, six of 15 DDFT on arterial contrast CT, eight of 11 DDFT on T1‐w MRI, and six of 11 DDFT on T2‐w/STIR MRI. Positron emission tomography was in better agreement with arterial contrast CT (Kappa‐weighted 0.40) and T2‐w/STIR MRI (0.35) than with noncontrast CT (0.28) and T1‐w MRI (0.20). Maximal standardized uptake values of lesions ranged from 1.9 to 4.6 with a median of 3.1. Chronic lesions with scar tissues identified on noncontrast CT or T1‐w MRI did not have increased 18 F‐FDG uptake. These results demonstrated that 18 F‐FDG PET agreed more closely with modalities previously used to detect active tendon lesions, i.e. arterial contrast CT and T2‐w/STIR MRI. 18 Fluorine‐fluorodeoxyglucose PET can be used to identify metabolically active DDFT lesions in horses.